Regulatory B cells in anti-tumor immunity - Zhang, Yu; Gallastegui, Nicolas; Rosenblatt, Joseph D (International immunology, 2015)
Advances in understanding of the immune microenvironment have highlighted the role of immunosuppressive T cell, myeloid, dendritic and monocytic sub-populations in inhibition of the anti-tumor immune response. The role of B cells in modulating the immune response to solid tumors as well as lymphoid malignancies is less well understood. Murine models of autoimmune disease have defined B regulatory cell (Breg) subsets with immune suppressive activity, including B cell subsets that express IL-10, and transforming growth factor-β, which can facilitate T regulatory cell recruitment and expansion. Multiple murine tumor models point to the existence of similar immune suppressive B cell sub-populations that can migrate into tumor deposits and acquire an immune suppressive phenotype, which then leads to attenuation of the local anti-tumor immune response. Other murine models of viral or chemically induced skin carcinogenesis have identified a pivotal role for B cells in promoting inflammation and carcinogenesis. While many human solid tumors demonstrate significant B cell infiltration and/or tertiary lymphoid structure formation, the functional properties of tumor-infiltrating B cells and their effects on immunity are poorly understood. Recent successes in early Phase I/II trials using anti-checkpoint inhibitor antibodies such as nivolumab or pidilizumab directed against PD-1 in the setting of Hodgkin's and non-Hodgkin's lymphomas validate the therapeutic utility of reversing B cell-mediated immune suppression. Further studies to define Breg subsets, and mechanisms of suppression, may provide new avenues for modulation of the immune response and meaningful therapeutic intervention in both lymphoid and solid tumors.